ABC of palliative care - Fallon, Marie; O'Neill, Bill (BMJ Publishing Group, 1998)
Addresses the core issues in managing chronically suffering patients, from prehospital care in the home through to the last 48 hours. With chapters on pain, nutritional problems, confusion and anxieties, emergencies, carers and bereavement, this is a comprehensive guide for all looking after patients with terminal illnesses.
Keywords: BELEST NESNESITELNÁ; paliativní péče; péče o umírající; geriatrie; nezvladatelná bolest; ošetřovatelství; anesteziologie a intenzivní lékařství; management bolesti; Palliative Care; Terminal Care; Pain Management; Pain, Intractable; Pain; bolest